POTENCIAL DO SEBO BOVINO RONDONIENSE COMO MATÉRIA PRIMA PARA PRODUÇÃO DE BIODIESEL EM ARIQUEMES – RO - Meneguetti, Naila Fernanda Sbsczk Pereira; Zan, Renato André; Meneguetti, Dionatas Ulises de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707636 The biodiesel is an alternative oil, that’s produced by the reaction chemical between an originallyvegetable or animal and alcohol (methyl or ethyl), reaction called of transesterification. Thepresent study have the objective of looking for potential of bovine fat Rondoniense in the fairregard raw material of production biodiesel. The survey was held of direct form, through visits atRondoniense cold stores. Through of information’s realized throughout quantitative analysis,comparing capacity of production of company De Paula Biodiesel with amount the production offat companies surveyed. The study led in consideration the daily and monthly production, theanimal fat produced slaughterhouse and cold stores evaluating a number of slaughter dailyaccomplished, and for each animal dead get in media 10kg of fat, where they got the number of133.327Kg of fat daily, leading in consideration that for each Kg of fat it is produced 0,95lt of biodiesel. The raw material is enough to produce 123.660lt, more than double of daily production,showing a big potential raw material available on the cold stores. Has been found the potential ofbovine fat Rondoniense like raw material for production of the biodiesel, were satisfactorysupplying more than the double of production maxima of the company, being the cold storesMinerva e Cooperativa Construção, the biggest producers of fat, having as a principal cityAriquemes – RO.